Towards new decolonial methodologies for intercultural dialogue. The problem of language in the Jñatro communities of central Mexico. (Interstices of politics and culture. Latin American interventions, 2019)
What is stated in this work seeks to influence and propose theoretical and methodological alternatives that help to find various alternatives to address intercultural work. In this sense, if we understand interculturality as a theoretical subject that seeks symbolic, territorial, epistemological and sensitive contact between various human historicalities, the inner theoretical work to this involves the planning of methodologies through which the knowledge produced from these contacts allows the transformation of existential dimensions among those who are meddled in this dynamic of change. Thinking about the above, this work seeks to propose or address an essential theme for intercultural dialogue: the problem of language and oral tradition, basic and fundamental elements of intercultural dialogue. To this end, it proposes as a methodological tool, the approach on this subject since what has been defined in this work as "transgression". This concept contrasts sharply with the vast majority of theoretical approaches based on a "language ideology" formalized as a method of controlling meanings. With this we seek to address processes of resistance present in the oral accounts of the Jñatro communities of central Mexico that are reproduced from a "collective hermeneutics" that gives meaning to them.